In Love and War: Nursing Heroes - Byrski, Liz (2015)
In the aftermath of the Battle of Britain, airmen filled a small Sussex town where pioneering plastic surgeon Archibald McIndoe established revolutionary surgical and therapeutic treatments. For the child Liz Byrski, the burnt faces of these airmen filled her nightmares. In her late sixties, Liz returned to make peace with her memories and to speak not only with the survivors – known as the Guinea Pig Club – but with the nurses who played a vital and unorthodox role in their treatment, sometimes at a significant personal cost. PRAISE FOR THE BOOK 'This is a book about the heroes and heroines who unflinchingly met the demands and challenges of their day ... a remarkable and moving story’ Professor Fiona Wood, AM 'Her strength as a writer of substance shines through in this easy-to-read account of her investigation into the Guinea Pigs Club men and the women who nursed them.' The West Australian ‘With impressive skill, Liz Byrski has combined memoir, archival research and interviews to produce one of the best books I’ve read about the complex casualties and consequences of war’ New Zealand Listener ‘Byrski anatomises the heroic mythology of the Battle of Britain and the medical treatment provided to severely burned RAF airmen’ Weekend Australian